Keeping milk clean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Gabriel Karanja, a milk trader and dairy producer in Kenya, and Eliana Mushi of a milk buying group in Tanzania, explain how dairy farmers can keep their milk free of dirt and other contaminants.